The ovarian cancer-associated microbiome contributes to the tumor’s inflammatory microenvironment - Zhang, Min; Mo, Jiahang; Huang, Wu; Bao, Yiting (Frontiers in Cellular and Infection Microbiology, 2024)
A growing body of research has established a correlation between tumors and persistent chronic inflammatory infiltration. As a primary instigator of inflammation, the majority of microbiomes naturally residing within our bodies engage in a mutually beneficial symbiotic relationship. Nevertheless, alterations in the microbiome's composition or breaches in the normal barrier function can disrupt the internal environment's homeostasis, potentially leading to the development and progression of various diseases, including tumors. The investigation of tumor-related microbiomes has contributed to a deeper understanding of their role in tumorigenesis. This review offers a comprehensive overview of the microbiome alterations and the associated inflammatory changes in ovarian cancer. It may aid in advancing research to elucidate the mechanisms underlying the ovarian cancer-associated microbiome, providing potential theoretical support for the future development of microbiome-targeted antitumor therapies and early screening through convenient methods.